The SDR Interest Rate Basket : Proposed Change of the Representative Interest Rate for the Euro and Amendment to Rule T-1(C). (Policy Papers; Policy Paper ;, 2014)
The three-month Eurepo interest rate, the euro component of the SDR interest rate basket, will be discontinued as of the end of 2014. The three-month Eurepo rate, administered by the European Money Market Institute (EMMI), has been the representative interest rate instrument of the euro area in the SDR interest rate basket since 2006. However, faced with a significant shrinking in the number of banks participating in the rate-setting panel, the EMMI announced last month that the Eurepo interest rate will be discontinued after December 31, 2014. This paper proposes to replace the three-month Eurepo rate in the SDR interest rate basket with a transactions-based three-month interest rate. Staff has consulted with the European Central Bank (ECB), which recommends to replace the Eurepo rate with a three-month spot rate derived from the secondary market yield curve covering euro area government bonds rated either investment grade or AA and above. In staff's view, the latter option (AA and above) would be most comparable to the other instruments in the SDR interest rate basket and would have characteristics that are most consistent with previous Board guidance for selection of financial instruments in the SDR basket. The proposed change would be implemented by an amendment to Rule T-1(c), requiring a 70 percent majority of the total voting power.